Pelaksanaan Pemberian Aromaterapi Lemon terhadap Penurunan Frekuensi Mual dan Muntah pada Ibu Hamil Trimester I di Puskesmas Biru-Biru Tahun 2025 - Tri Marini; Betty Mangkuji; Ardiana Batubara; Jujuren Br Sitepu; Tengku Sri Wahyuni; Suryani Suryani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Pregnancy is a natural process that occurs from conception to the growth of the fetus in the womb. Lemon aromatherapy is an alternative method to reduce nausea and vomiting. When essential oils are inhaled, volatile molecules will carry the aromatic elements contained in the oil to the tip of the nose. The aim is to determine the effect of lemon aromatherapy on the frequency of reducing nausea and vomiting in pregnant women in the first trimester at the Biru-Biru Community Health Center. This study used the Quasy Experiment method with a One Group Pretest Posttest Design by conducting a Pretest before giving treatment and a Posttest after giving treatment. The population of this study were pregnant women who experienced nausea and vomiting in pregnant women in the first trimester at the Biru-Biru Community Health Center. Sampling was carried out using a total sampling technique, resulting in 30 pregnant women experiencing nausea and vomiting. The results obtained from the study, respondents who did not experience nausea and vomiting after being given lemon aromatherapy were 14 people, 11 people experienced mild nausea and vomiting, and 5 people experienced moderate nausea and vomiting. The analysis used in this study was the Wilcoxon test, which obtained a value (p = 0.000 < 0.05) and there was an effect of lemon aromatherapy on the frequency of reducing nausea and vomiting in pregnant women at the Biru-Biru Community Health Center.